Pengaruh Beban Kerja, Lingkungan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Pt. Satria Nusantara Sakti (International Forum of Researchers and Lecturers, 2023)
The purpose of this study was to determine the effect of workload, work environment, and work motivation on the performance of employees at PT. Satria Nusantara Sakti. This study uses a quantitative approach with the category of causal associative research. The population in this study are employees of PT. Satria Nusantara Sakti as many as 35 people, with the entire population being sampled. Data collection was carried out by distributing questionnaires. The data analysis technique used multiple linear regression analysis with the help of the SPSS 22 program. The results showed that workload had a positive and significant effect on employee performance, the work environment had a positive and significant effect on employee performance, and work motivation had a positive and significant effect on employee performance. The results of the study also show that workload, work environment, and work motivation simultaneously influence employee performance.